Education in the British West Indies - Williams, Eric Eustace (University Place Bookshop, 1968)
This book presents the basic ideas outlined in a memorandum prepared by the author for a sub-committee of the Committee appointed to investigate the position of higher education in the colonies and to make recommendations with regard to its extension. Although the study originated specifically from the idea of a British West Indian university, it also treats the general level of education in the community, and the economic, social, and political characteristics of the community that the education was designed to serve
First published in 1950. Reprinted 1994 by A&B Book Publishers
Keywords: History of education